Blockchain‐based traceability and demand for U.S. beef in China. Issue 1 (28th December 2020) - Lin, Wen; Ortega, David L.; Ufer, Danielle; Caputo, Vincenzina; Awokuse, Titus
Abstract: Amid stringent traceability requirements and a nearly 14‐year ban, the U.S. beef industry is rebuilding its market presence in China. Blockchain technology offers a responsive means of meeting Chinese import traceability requirements while also addressing consumers' food safety concerns. We evaluate Chinese demand for U.S. beef and blockchain‐based traceability and find that a sizeable segment of the market (37%) is willing to pay a premium for U.S. beef that is traceable using blockchains. Results indicate that investments in traceability systems that utilize blockchain technology may be an effective way for producers to capture a significant market share in China.